Some Generalized Results on G_δ -diagonal Regular Spaces - Pralahad Mahagaonkar (International Journal of Mathematics And its Applications, 2015)
In this paper we constructed a space X possessing a regular G_δ-diagonal set of full measure, then the space X has a diagonal set if {(x,x):xX} and is regular in G_δ-set for X× X. We extend our result for some characterization of spaces with G_δ -diagonal set. Such a kind obtained by Borges.C.J.R [1], Cinder.J.G [2] and Zenor.P [5].